1997
DOI: 10.1073/pnas.94.5.1733
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of murine RNA polymerase I-specific TAF factors: Conserved interactions between the subunits of the species-specific transcription initiation factor TIF-IB/SL1

Abstract: Promoter selectivity for all three classes of eukaryotic RNA polymerases is brought about by multimeric protein complexes containing TATA box binding protein (TBP) and specific TBP-associated factors (TAFs). Unlike class II-and III-specific TBP-TAF complexes, the corresponding murine and human class I-specific transcription initiation factor TIF-IB͞ SL1 exhibits a pronounced selectivity for its homologous promoter. As a first step toward understanding the molecular basis of species-specific promoter recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 22 publications
4
77
0
Order By: Relevance
“…Western blots of the matrix-bound fraction with anti-TAF I 95 antibodies (14) revealed that the TIF-IB complex was specifically and efficiently retained on the UBF affinity matrix (Fig. 6B, lanes 1 and 2).…”
Section: Results Prb Represses Rdna Transcription In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Western blots of the matrix-bound fraction with anti-TAF I 95 antibodies (14) revealed that the TIF-IB complex was specifically and efficiently retained on the UBF affinity matrix (Fig. 6B, lanes 1 and 2).…”
Section: Results Prb Represses Rdna Transcription In Vitromentioning
confidence: 99%
“…After incubation for 2.5 h at 4°C, the resins were extensively washed with buffer AM-100-0.1% NP-40 and the beads were boiled in SDS-containing buffer and applied to SDS-8% polyacrylamide gels. Pol I and TIF-IB were detected on immunoblots with purified antibodies against RPA116, the second largest subunit of mouse Pol I (37), or antibodies raised against mouse TAF I 95 (14).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an alternative model was proposed (Grummt, personal communication) based on the finding that mitosis-specific phosphorylation of the hTAF I 110 subunit of SL1 by p34 cdc2 / cyclin B kinase causes repression of rDNA transcription. SL1 is essential for the assembly of preinitiation complexes at the rDNA promoter (Eberhard et al, 1993;Heix et al, 1997) by recruiting RNA pol I associated with two essential factors, TIF-IA and TIF-IC, to the template (Schnapp and Grummt, 1991). Similar mechanisms of transcription repression by mitosisspecific phosphorylation have been found for equivalent TBP-TAF complexes, TFIID of RNA pol II and TFIIIB of RNA pol III, in which assembly of preinitiation complexes is inhibited (Hartl et al, 1993;Gottesfeld et al, 1994;White et al, 1995;Leresche et al, 1996;Segil et al, 1996; reviewed by Gottesfeld and Forbes, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Speciesspecific gene expression in human and mouse is restricted to some genes involved in, e.g., immune and xenobiotic response, and for polymerase I-dependent transcription of rRNAs (27)(28)(29). In such cases, one could alternatively rescue with a BAC carrying the same gene containing silent mutations or a modified 3Ј UTR.…”
Section: Alternative Splicing and Physiological Expression Of Murine mentioning
confidence: 99%